The Influence of Exchange Rate and Inflation on the Economic Growth in Bengkalis Regency - Nurul Fajar; Wan Junita Raflah (Politeknik Kampar, 2024)
This study aims to analyze the effect of inflation and exchange rates on economic growth in Bengkalis Regency. This study uses a Quantitative method, and the type of data used is secondary data, which means that the data that has been finished or published is taken from BPS (Central Statistics Agency) Indonesia data and also Bengkalis in numbers with period 19 years (2003-2021). Data processing used the IBM SPSS version 25 application with multiple linier regression analysis testing which included T-test, F-test, and the Coefficient Determination (R2). The results of this study indicate that: 1) Exchange Rate has a positive and significant effect on economic growth in Bengkalis Regency, 2) Inflation has a negative and significant effect on economic growth in Bengkalis Regency. Therefore, if the Exchange Rate increases, it will have a positive impact on economic growth, as well as inflation, if it increases, it will have a negative effect on economic growth in Bengkalis Regency, 3) the coefficient of determination (R2) is 0.931. This means that exchange rate and inflation affect economic growth in Bengkalis regency by 93.1% while the remaining 6.9% is influenced by other variables not examined in this study.